Burden of premature ventricular contractions beyond nonsustained ventricular tachycardia is related to the myocardial extracellular space expansion in patients with hypertrophic‐cardiomyopathy. Issue 11 (20th August 2020) - Chung, Hyemoon; Park, Chul‐Hwan; Kim, Yoonjung; Kim, Jong‐Youn; Min, Pil‐Ki; Yoon, Young Won; Lee, Kyung‐A; Lee, Byoung Kwon; Hong, Bum‐Kee; Kim, Tae Hoon; Rim, Se‐Joong; Kwon, Hyuck Moon; et al.
Abstract: Background: Although nonsustained ventricular tachycardia (NSVT) is a risk factor for sudden cardiac death in hypertrophic‐cardiomyopathy (HCM), the impact of premature ventricular contraction (PVC) burden, in the absence of NSVT, is not well‐known. Hypothesis: PVC burden may be associated with myocardial fibrosis and genetic mutations in patients with HCM. Methods: Of the 212 patients prospectively enrolled to the HCM registry of genetics, 84 were evaluated with both cardiac magnetic resonance, 24‐hour Holter monitoring and genetic analysis. Among them, 71 patients have not been diagnosed with NSVT. Results: Patients with NSVT (n = 13) had a higher late gadolinium enhancement (LGE) amount, extracellular volume fraction (ECV), and prevalence of sarcomere mutations compared with patients without NSVT. Among patients without NSVT, those with LGE (n = 46) had a higher total PVC (109 ± 332 vs 7 ± 13, P = .003) and PVC burden (0.114 ± 0.225 vs 0.008 ± 0.014%, P = .003) during 24‐hour Holter monitoring compared with others. The %LGE and global ECV were correlated with PVC burden (r = 0.377, P = .001; r = 0.401, P = .001). The optimal cutoff value for PVC number for LGE was 45 (37.0% and 100% sensitivity and specificity, respectively) with 0.733 of the area under the receiver operating characteristic‐curve ( P  < .001). Thick filament gene mutation was more prevalent in the higher PVC burden group (41.2% vs 16.7%, P = .048). Conclusion: Total PVC burden is significantly related to increase in myocardial fibrosis in HCM patients without NSVT.